Repetitive use of levosimendan for treatment of chronic advanced heart failure: clinical evidence, practical considerations, and perspectives: an expert panel consensus - Nieminen, M S; Altenberger, J; Ben-Gal, T; Böhmer, A; Comin-Colet, J; Dickstein, K; Edes, I; Fedele, F; Fonseca, C; García-González, M J; Giannakoulas, G; Iakobishvili, Z; et al. (International journal of cardiology, 2014)
BACKGROUND: The intravenous inodilator levosimendan was developed for the treatment of patients with acutely decompensated heart failure. In the last decade scientific and clinical interest has arisen for its repetitive or intermittent use in patients with advanced chronic, but not necessarily acutely decompensated, heart failure. Recent studies have suggested long-lasting favourable effects of levosimendan when administered repetitively, in terms of haemodynamic parameters, neurohormonal and inflammatory markers, and clinical outcomes. The existing data, however, requires further exploration to allow for definitive conclusions on the safety and clinical efficacy of repetitive use of levosimendan. METHODS AND RESULTS: A panel of 30 experts from 15 countries convened to review and discuss the existing data, and agreed on the patient groups that can be considered to potentially benefit from intermittent treatment with levosimendan. The panel gave recommendations regarding patient dosing and monitoring, derived from the available evidence and from clinical experience. CONCLUSIONS: The current data suggest that in selected patients and support out-of-hospital care, intermittent/repetitive levosimendan can be used in advanced heart failure to maintain patient stability. Further studies are needed to focus on morbidity and mortality outcomes, dosing intervals, and patient monitoring. Recommendations for the design of further clinical studies are made.
Keywords: stupeň závažnosti nemoci; Heart Failure; chronická nemoc; Vasodilator Agents; Pyridazines; hydrazony; lidé; srdeční selhání; pyridaziny; Severity of Illness Index; směrnice pro lékařskou praxi jako téma; Chronic Disease; Practice Guidelines as Topic; vazodilatancia; Hydrazones; Humans